Optimalisasi Penggunaan Media Sosial Dalam Pendidikan Kewarganegaraan - Maskarto Lucky Nara Rosmadi (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
This study aims to find out how social media can be optimized for use in citizenship education. The research method used is a qualitative method with a descriptive analytical approach. The results of the study show that the use of social media in civic education courses is not optimal, especially in its application. This is due to the lack of lecturers with a background in civic education and the absence of special education for lecturers who teach this subject. The role of the government, institutions and other relevant departments is very necessary so that the Civic Education courses in shaping the younger generation who have high character and nationalism can be realized both in theory and in daily life.